how to solve this x2y''-xy'+y=2x by variation of parameter
This equation is euler-cauchy equation.
Substitute "y=x^{m}" into the homogenous equation.
"y''=m(m-1)x^{m-2}"
"x^2(m(m-1)x^{m-2})-x(mx^{m-1})+x^m=0"
"x^m(m^2-m-m+1)=0"
"x^m(m-1)^2=0"
"m=1"
Hence the solution of the homogenous equation is
Use method of variations of parameters "c_1=c_1(x), c_2=c_2(x)"
Suppose
"c_1'x+c_2'x\\ln x=0"Then
"y''=c_1'+c_2\\dfrac{1}{x}+c_2'\\ln x+c_2'"
"x^2c_1'+xc_2+x^2c_2'\\ln x+x^2c_2'-xc_1-xc_2\\ln x"
"-xc_2+c_1x+c_2x\\ln x=2x"
We have the system
Then
"-x^2c_2'\\ln x+x^2c_2'\\ln x+x^2c_2'=2x"
"c_2'x=2"
"c_2=\\int\\dfrac{2dx}{x}"
"c_1=-\\int\\dfrac{2\\ln xdx}{x}"
"c_1=-\\ln^2(x)+C_3"
"c_2=2\\ln(x)+C_4"
"y=x\\ln^2(x)+C_3x+C_4x\\ln(x)"
Comments
Leave a comment